Embryonic development and growth characteristics in juvenile rainbow trout (Oncorhynchus mykiss Wal.) originating from five different parent flocks - Savić Nebojša; Mikavica Dragan; Rogić Biljana (Agroznanje, 2012)
Five hatcheries (different parent flocks) were selected. Their fertilised roe was taken in the period from 13 December 2012 to 21 December 2012 and transported to salmonid spawning Klašnik Banja Luka, where it was placed under the same conditions as in the incubation development. All the females whose spawn was taken were 4 years old. The water temperature in the hatchery varied within narrow limits and ranged from 10.2 to 10.8o C. The embryonic development of the eye appearance varied from 176 (treatment 5) to 188 (treatment 1) degree days. The incubation period (from fertilisation to hatching) lasted from 260 degree days in the treatment of 4 to 292 degree days in treatments 1, 2 and 3. Mortality during the incubation period was extremely high in the treatment of 4 and was 60.79%, while in the other treatments it ranged from 4.19% to 10.80%. With transition to exogenous feeding, significant differences in terms of growth characteristics were found, which is epecially evident in different values of SGR and TGC. Using analysis of variance and t-test, statistically significant differences between mean weight and body length (=0.01) were determined in most combinations, indicating significant genetic heterogeneity of the analysed parent flocks.